Development of Critical Thinking Skills Through Problem-Based Learning Methods in Ushul Fiqh Subject at Madrasah Aliyah Negeri 2 Yogyakarta - Tsaaniyatush Shoolihah Fauzan (Al-Ard: Journal of Education, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) method in developing students' critical thinking skills in the Ushul Fiqh subject at Madrasah Aliyah Negeri 2 Yogyakarta. The study employs a qualitative approach with classroom action research method conducted in two cycles. The research subjects were 32 students from class XI IPA 3. Data collection techniques included observation, interviews, critical thinking skills tests, and documentation. The results showed that the implementation of the PBL method can enhance students' critical thinking skills in understanding Ushul Fiqh concepts. In cycle I, the average critical thinking skills score reached 72.5 with a good category, increasing to 84.3 in cycle II with an excellent category. Critical thinking skill indicators that experienced improvement included the ability to analyze, evaluate, and make inferences regarding Islamic legal issues. This study recommends the use of the PBL method as an effective learning alternative for the Ushul Fiqh subject.